Identifying Mechanisms of Resistance to Oncolytic Virotherapy in Acute Leukemia Through a Genome-wide CRISPR Screen - Rose, Elaine (Université d'Ottawa / University of Ottawa, 2018)
Approximately half of all adults diagnosed with acute leukemia (AL) relapse after standard chemotherapy, highlighting the need for alternative treatment options. We have previously shown that vaccination with irradiated autologous tumour cells infected with an oncolytic virus (OV) can elicit a durable, tumour specific, T cell- mediated response in a mouse model of AL. In the context of this AL infected cell vaccine (ICV) model, infection of autologous cells ex vivo with an OV is essential for stimulating a lasting immune response. While the murine AL line L1210 can be robustly infected with Maraba MG1, creating a potent infected cell culture, this ICV still has room for improvement as ICV-vaccinated mice with high tumour burden still die from leukemia. Therefore, we sought to utilize a genome wide CRISPR-Cas9 screen to identify genetic factors that mediate OV resistance in this model of AL. L1210 cells stably expressing Cas9 were transduced with the mouse GeCKOv2 library, which contains 130,209 gRNAs against 20,611 genes within the mouse genome. Following selection, cells were treated with Maraba MG1 and genomic DNA from resistant populations was sequenced to identify genes enriched in resistant cells relative to mock treated cells. Our screen identified several genes that mediate susceptibility to OV infection including those involved in viral entry (Ldlr), receptor-mediated endocytosis (Atp6v1g2), intracellular signaling (Cav1), the cytoskeleton (Filip1 and Tmod4), as well as autophagy and exosome production (Atg5). We aim to use the findings from this work to improve therapeutic efficacy in otherwise OV resistant tumour models as well as identify biomarkers, to determine the feasibility of administering an ICV using patient derived tumour cells.
Keywords: Leukemia; CRISPR; Virus